Examining the longitudinal influence of loneliness on healthcare utilization: evidence from Taiwan’s national health insurance data - Shiau-Fang Chao; Hui-Chuan Hsu; Chia-Le Yen; Bo-Yu Chen (BMC Geriatrics)
Abstract Background This study combines a nationally representative sample from Taiwan with four years of National Health Insurance (NHI) data to explore the distinctive impact of emotional and social loneliness on health service utilization, including outpatient visits for mental health, general outpatient visits, emergency room (ER) visits, and hospitalization. Methods Data were drawn from the 2015 Taiwan Longitudinal Survey on Aging (TLSA) and merged with participants’ NHI records from 2015 to 2018. The analysis used logistic regression for binary outcomes and negative binomial regression for counts. Results Results show that higher emotional loneliness in 2015 was associated with increased outpatient mental health visits over time and more general outpatient visits within the same year. Conversely, higher social loneliness in 2015 reduced the likelihood of seeking ER care in 2015. Conclusions By merging national data and distinguishing emotional from social loneliness, this study offers insights into their differential impacts on healthcare utilization among older adults in Taiwan. It emphasizes the importance of addressing loneliness to improve physical and mental well-being and optimize the effective utilization of healthcare resources.